Effect of Molecular Structure of Oil on the Film Thickness during Rolling - Takamichi Watanabe (Japanese Society of Tribologists, 2009)
In recent years, metal working oil is required to have lower viscosity and higher lubricity than ever. Controlling oil film thickness is one of the most important in metal working. In this study, we investigated the effect of molecular structure and molecular weight distribution of oil on both lubricity and oil film thickness on friction surface during rolling. Oil film thickness was measured for three oils with the different molecular structures in spite of the same kinematic viscosity. In this result, the polyisobutylene with relative rigid structure formed the thickest film of the three oils. Oils with broad molecular weight distribution (wide-ranged oil) were formulated by mixing a few polyisobutylenes which have different molecular weight distribution. A film thickness with wide-ranged oil was eight times as thick as one with a narrow molecular weight distribution (narrow-ranged oil) in spite of the same viscosity. Increase in the difference of molecular weight increased the film thickness. We could reduce a friction coefficient during rolling even with a low viscosity oil, using a wide-ranged oil.